2021
DOI: 10.1021/acs.jpclett.1c00287
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively Switchable pH-Sensitive Photoluminescence of Carbon Nanodots

Abstract: pH sensing plays a key role in the life sciences as well as the environmental, industrial, and agricultural fields. Carbon nanodots (C-dots) with small size, low toxicity, and excellent stability hold great potential in pH sensing as nanoprobes due to their intrinsic pHsensitive photoluminescence (PL). Nonetheless, the undesirable sensitivity and response range of C-dot PL toward pH cannot meet the requirements of practical applications, and the unclear pH-sensitive PL mechanism makes it difficult to control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…Previous reports showed that the protonation and deprotonation of functional groups on the surface of CDs could change the energy level, aggregation, and electron/proton transfer, giving rise to a change in the PL properties. , Here, the fluorescence decay curves of CDs 1 at different pH values were recorded to further study the possible mechanism of the unique pH-sensitive PL. For the emission site with an ∼500 nm peak, which is sensitive toward pH (ranging from 1.6 to 3.0), the fluorescence lifetime (τ) increased from 2.95 ns (pH 1.6) to 7.54 ns (pH 3.0) as the pH increased from 1.6 to 3.0 (Figure a and Table S2).…”
Section: Resultsmentioning
confidence: 95%
“…Previous reports showed that the protonation and deprotonation of functional groups on the surface of CDs could change the energy level, aggregation, and electron/proton transfer, giving rise to a change in the PL properties. , Here, the fluorescence decay curves of CDs 1 at different pH values were recorded to further study the possible mechanism of the unique pH-sensitive PL. For the emission site with an ∼500 nm peak, which is sensitive toward pH (ranging from 1.6 to 3.0), the fluorescence lifetime (τ) increased from 2.95 ns (pH 1.6) to 7.54 ns (pH 3.0) as the pH increased from 1.6 to 3.0 (Figure a and Table S2).…”
Section: Resultsmentioning
confidence: 95%
“…Under extreme pH conditions, the rapid oxidation or inactivation of N-MQDs is responsible for the decreased PL emission. 41,42…”
Section: Resultsmentioning
confidence: 99%
“…Under extreme pH conditions, the rapid oxidation or inactivation of N-MQDs is responsible for the decreased PL emission. 41,42 In addition, the emission wavelength of the N-MQDs exhibited very small redshift (∼5 nm) when the pH decreased from 12.1 to 2.0 under excitation at 320 nm. When excited at 365 nm, the fluorescence peak of the N-MQDs showed a pronounced redshift of 50 nm from 464 to 514 nm (Fig.…”
Section: Characterization Of Qdsmentioning
confidence: 95%
See 1 more Smart Citation
“…1,2 C-dots have sparked enormous research interest due to their advanced physical and chemical properties, including ultra-small size, excellent solvent solubility, biocompatibility, continuous and broad absorption spectra, high luminescent activity, significantly improved photostability, and environmental friendliness. [3][4][5][6][7][8] As the alternative to metal and semiconductor based luminescent nanomaterials, C-dots with their pronounced and tuneable photophysical properties [9][10][11] have been widely used for bioimaging, [12][13][14] drug delivery, [14][15][16] sensing, [17][18][19] catalysis [20][21][22] and optoelectronic applications. 3,[23][24][25][26][27] The functionalities of C-dots are connected with their structures.…”
Section: Introductionmentioning
confidence: 99%